PENGARUH KINERJA DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS MUHAMMADIYAH GRESIK - NAILIL FATCHIYAH (Jurnal Manajerial, 2018)
The aim of this study is to test the influence of faculty performance on student learning motivation of Management, Faculty of Economics, University of Muhammadiyah Gresik. By using a sample of 83 respondents. Testing is done by using multiple regression analysis. The results of multiple regression showed that the performance of lecturers includes pedagogical, professional competence, personal competence and social competence significantly associated with students' learning motivation.